Rehabilitacija bolnikov z nevromiopatijo kritično bolnih - Novak, Primož (Rehabilitacija (Ljubljana), 2010)
Critical illness polyneuropathy and myopathy (CIPM) frequently develops in patients hospitalized in intensive care units. The number of these patients admitted to our Institute is increasing. The article presents a review of the published studies on rehabilitation of these patients. A survey of the electronic bibliographic databases revealed only a few relevant articles on rehabilitation of CIPM patients. Therefore, a review of published studies on rehabilitation of critical illness patients where polyneuropathy and myopathy are not specifically mentioned was added. According to the published studies and reports, as well as our experience, CIPM patient's function and activities improve within a relatively short period of rehabilitation.
Keywords: miopatije; neurology; nevrologija; nevropatije; rehabilitacija; vocational rehabilitation